Association of cannabinoid receptor modulation with normal and abnormal skeletal remodelling: A systematic review and meta-analysis of in vitro, in vivo and human studies. (January 2022) - Sophocleous, Antonia; Yiallourides, Michael; Zeng, Feier; Pantelas, Pantelis; Stylianou, Eleni; Li, Boya; Carrasco, Giovana; Idris, Aymen I.
Abstract: To address the inconsistent findings from studies that used different models to explore the role of classical cannabinoid type 1 (CB1) and 2 (CB2) receptors in skeletal remodelling, we searched Medline, Web of Science and Embase for relevant studies from inception to June 23, 2020. We identified 38 in vitro, 34 in vivo and 9 human studies. A meta-analysis of in vitro studies showed that exposure to the inverse-agonists AM251 (mean difference [MD]:−26.75, 95% confidence interval [CI]:−45.36, −8.14, p = 0.005), AM630 (standardised[std.] MD:−3.11, CI:−5.26, −0.97, p = 0.004; SR144528, std.MD:−4.88, CI −7.58, −2.18, p = 0.0004) and CBD (std.MD:−1.39, CI −2.64, −0.14, p = 0.03) is associated with reduced osteoclastogenesis, whereas the endocannabinoid 2-AG (std.MD:2.00, CI:0.11–3.89, p = 0.04) and CB2-selective agonist HU308 (MD:19.38, CI:11.75–27.01, p < 0.00001) were stimulatory. HU308 also enhanced osteoblast differentiation (std.MD:2.22, CI:0.95–3.50, p = 0.0006) and activity (std.MD:2.97, CI:1.22–4.71, p = 0.0008). In models of bone loss, CB1/2 deficiency enhanced peak bone volume (std.MD:3.70, CI:1.77–5.63, p = 0.0002) but reduced bone formation (std.MD:−0.54, CI:−0.90, −0.17, p = 0.004) in female mice. In male rats, CB1/2 deficiency (std.MD:2.31, CI:0.30–4.33, p = 0.02) and AM251 or CBD treatments (std.MD:2.19, CI:0.46–3.93, p = 0.01) enhanced bone volume. CB1/2 deficiency (std.MD:9.78, CI:4.96–14.61, p < 0.0001) and AM251 or AM630 treatments (std.MD:28.19, CI:19.13–37.25, p < 0.0001) were associated with osteoprotection. The CB2-selective agonists JWH133 and 4Q3C enhanced bone volume in arthritic rodents (std.MD:14.45, CI:2.08–26.81, p = 0.02). In human, CB2 SNPs (AA:rs2501431, MD:−0.28, CI:−0.55, −0.01, p = 0.04; CC:rs2501432, MD:−0.29, CI:−0.56, −0.02, p = 0.03) were associated with reduced bone mineral density, however the association of Marijuana use remains unclear. Thus, CB1/2 modulation is associated with altered bone metabolism, however findings are confounded by low study number and heterogenicity of models. Graphical Abstract: ga1 Highlights: Pharmacological and genetic manipulation of CB1/2 receptors altered bone cell activity in vitro. Pharmacological and genetic manipulation of CB1/2 receptors altered bone volume in vivo Single nucleotide polymorphisms in CNR2 gene affects bone mineral density (BMD) in human. The association of marijuana use with bone mineral density remains unclear. CB1/2 modulation is associated with normal and abnormal skeletal remodelling.